Photoperiodically driven transcriptome-wide changes in the hypothalamus reveal transcriptional differences between physiologically contrasting seasonal life-history states in migratory songbirds - Aakansha Sharma (Nature Portfolio, 2021)
Abstract We investigated time course of photoperiodically driven transcriptional responses in physiologically contrasting seasonal life-history states in migratory blackheaded buntings. Birds exhibiting unstimulated winter phenotype (photosensitive state; responsive to photostimulation) under 6-h short days, and regressed summer phenotype (photorefractory state; unresponsiveness to photostimulation) under 16-h long days, were released into an extended light period up to 22 h of the day. Increased tshβ and dio2, and decreased dio3 mRNA levels in hypothalamus, and low prdx4 and high il1β mRNA levels in blood confirmed photoperiodic induction by hour 18 in photosensitive birds. Further, at hours 10, 14, 18 and 22 of light exposure, the comparison of hypothalamus RNA-Seq results revealed transcriptional differences within and between states. Particularly, we found reduced expression at hour 14 of transthyretin and proopiomelanocortin receptor, and increased expression at hour 18 of apolipoprotein A1 and carbon metabolism related genes in the photosensitive state. Similarly, valine, leucine and isoleucine degradation pathway genes and superoxide dismutase 1 were upregulated, and cocaine- and amphetamine-regulated transcript and gastrin-releasing peptide were downregulated in the photosensitive state. These results show life-history-dependent activation of hypothalamic molecular pathways involved in initiation and maintenance of key biological processes as early as on the first long day.